The socio-economic organisation of the Urartian Kingdom - Çifçi, Ali. (Culture and History of the Ancient Near East, 2017)
In The Socio-economic Organisation of the Urartian Kingdom , Ali Çifçi presents a detailed study of the life of the highland communities of eastern Anatolia, Armenia and north-west Iran between the 9th and 6th centuries BC. In doing so, the author uses archaeological excavations, surveys, and textual evidence from both Urartian and Assyrian sources, as well as original ethnographic observations, within the context of the geographical setting of the Urartu Kingdom. This book investigates various aspects of the Urartian Kingdom from its economic resources and the movement of commodities (agriculture, animal husbandry, metallurgy, trade, et cetera) to the management of those resources and the administrative organisation of the state. This includes the Urartian concept of kingship and the king's role in administration, construction, the division of the kingdom, as well as the income generated by warfare. "There are several key philological and archaeological works that propel the field of Urartian studies and provide dialogue partners for Urartologists and historians of Anatolia and the ancient Near East...Ali Çifçi's The Socio-Economic Organisation of the Urartian Kingdom can be included as a partner in dialogue when researching Urartu and Iron Age Anatolian archaeology..." Selim Ferruh Adalı, Social Sciences University of Ankara, in Bryn Mawr Classical Review 2018.07.22.